Frequency and Type of Malaria in All Febrile Children Up to Five Years of Age (Medical Forum Monthly, 2024)
Objective: To determine the frequency and type of malaria in all febrile children up to five years of age visiting the OPD of NICH.Study Design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at the Emergency and Outpatient Department of National Institute of Child Health, Karachi from 1st July 2016 till 31st December 2016.Materials and Methods: All children of 1 month to 5 years of age of either gender having history of fever as primary complain since 24 hours or more were enrolled. Laboratory test was performed and presence of malaria (yes/no) and type of malaria (if malarial positive) was noted.Results: Out of total 253 children, majority of the patients were presented with ≤2.5 years of age (Mean age 1.48 ±.500 years). The proportion of female children was lower 102 (40.3%) than that of male children 151 (59.7%). Frequency of malaria was found in 17 (6.76%) patients. Frequency of malaria was found in 17 (24.1%) patients. Among these 17 malaria cases, 2 (11.76%) had falciparum while 15 (88.23%) had vivax type of malaria. Educational status of mother (p-value 0.003), father (p-value 0.038) and economic status (p-value <0.001) were significant factors associated with presence of malaria in children.Conclusion: The frequency of malaria was found to be higher with predominance of vivax type in all febrile children up to five years of age visiting the OPD of NICH